2018
DOI: 10.1016/j.plefa.2017.01.001
|View full text |Cite
|
Sign up to set email alerts
|

BanI polymorphism of cytosolic phospholipase A2 gene and somatic symptoms in medication-free acute depressed patients

Abstract: Somatic symptoms are commonly seen in patients with major depressive disorder (MDD) and might be associated with inflammatory activation. Cytosolic phospholipase A2 (cPLA2) and cyclo-oxygenase-2 (COX-2) are the key enzymes in the metabolism of polyunsaturated fatty acids (PUFAs), which in turn may play an important role in inflammation and somatic symptoms in depression. This study investigated the effects of BanI polymorphism of cPLA2 gene and COX-2 rs4648308 genotypes on somatic symptoms and inflammatory mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Interestingly, the results are also consistent with our recent findings that somatic anxiety is associated with omega-3 PUFA deficits and the genetic risks of PUFA metabolic enzyme cytosolic phospholipase A2 in major depressive disorder 62,63 and interferon α-induced neuropsychiatric syndrome. 63,64 Brain membranes contain a high proportion of omega-3 PUFAs and their derivatives and most animal and human studies suggest that a lack of omega-3 PUFAs in the brain might induce various behavioral and neuropsychiatric disorders, 16,[65][66][67][68][69][70] including anxiety-related behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the results are also consistent with our recent findings that somatic anxiety is associated with omega-3 PUFA deficits and the genetic risks of PUFA metabolic enzyme cytosolic phospholipase A2 in major depressive disorder 62,63 and interferon α-induced neuropsychiatric syndrome. 63,64 Brain membranes contain a high proportion of omega-3 PUFAs and their derivatives and most animal and human studies suggest that a lack of omega-3 PUFAs in the brain might induce various behavioral and neuropsychiatric disorders, 16,[65][66][67][68][69][70] including anxiety-related behaviors.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it has been suggested that the genetic variations in phospholipase A2 and cyclooxygenase 2 genes, enzymes responsible for PUFAs metabolism, have been associated with the risk of inflammation-induced depression, possibly by lowering the levels of n-3 PUFAs such as EPA and DHA, which have anti-inflammatory properties, in both MDD patients [108] and medically ill patients treated with the pro-inflammatory cytokine interferon- [109]. A recently published practice guideline for clinical use of Omega-3 in Youth: ADHD, ASD and Depression 475 n-3 PUFAs in MDD [110] suggested that n-3 PUFAs in MDD treatment should be considered for special populations including pregnant women [5,[111][112][113], and children.…”
Section: Pre-clinical Studiesmentioning
confidence: 99%
“…Activation of phospholipases enhances the production of prostaglandin E2, which plays an anti-inflammatory role in the brain [ 70 ], consistent with the over-expression in MIA relative to Control pigs. Moreover, PLA2GA was over-expressed in the peripheral blood mononuclear cells in SSD compared to control individuals [ 71 ], and genetic variants of this family have been associated with depression [ 72 ]. Furthermore, also impacted by MIA were genes in the protein kinase cGMP-dependent family, including PRKG1 , PRKG2 , and PRKCB ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%